2015
DOI: 10.22146/ijbiotech.7565
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Fucoidan on Gastric Ulcer

Abstract: Hyperacidity causes gastric injury, and in severe situations, ulcer could develop. The growth factors known as the basic fibroblast growth factor (bFGF) and the epidermal growth factor (EGF) have been recognized to promote ulcer healing. Fucoidan is extracted from a brown seaweed of Okinawa called Mozuku or Cladosiphon okamuranus. Fucoidan is effective for the healing of gastric ulcers by inducing epithelial cells to produce growth factors. The aim of this study is to explore the efficacy of fucoidan in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similarly, in a rat model of acute colitis, an orally delivered polysaccharide food supplement containing fucoidan reduced monocyte numbers and improved clinical markers of colitis [ 22 ]. Fucoidan is also known to protect against aspirin-induced gastric ulcers in a rat model [ 23 ] and is known from pre-clinical and clinical investigations to inhibit gastric pathogens [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a rat model of acute colitis, an orally delivered polysaccharide food supplement containing fucoidan reduced monocyte numbers and improved clinical markers of colitis [ 22 ]. Fucoidan is also known to protect against aspirin-induced gastric ulcers in a rat model [ 23 ] and is known from pre-clinical and clinical investigations to inhibit gastric pathogens [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 15 revealed that fucoidan protected against alcohol‐induced gastric mucosal damage. Juffrie et al 16 further verified the effect of fucoidan on ulcer healing and the improvement of ulcer symptoms. Other studies have also revealed that fucoidan can increase intestinal microbial diversity and modulate the microbiota composition 17 …”
Section: Discussionmentioning
confidence: 93%
“…Noteworthily, efficacies of sulfated polysaccharides in treating gastric diseases have been confirmed in clinical research. Dietary supplement of Cladosiphon okamuranus fucoidan for 3 weeks could improve the ulcer healing of patients with severe GU (Juffrie et al., 2011). GU patients treated with a sulfated polysaccharide exhibited dominant decreases in ulcer size per day (Zimmon et al., 1969).…”
Section: Gastroprotective Activity Of Polysaccharidesmentioning
confidence: 99%